FLOODING MENACE ON SOCIAL ENVIRONMENTAL DEVELOPMENT: CREATING AWARENESS THROUGH MUSIC - Okafor, Enoh (Revista Prâksis, 2025)
Climate manifestations resulting in floods causes social environmental catastrophes which enormously impacts social environmental development. Various medium of climate manifestations dissemination are available among these media is music but in Nigeria this media is seldomly explored by the government. The study focusses on awareness creation through music medium to educate Nigerian populace on the effects of climate menace. The study analyzes two song lyrics as primary sources. Both songs provided useful information on the effects of climate manifestation as well as resolutions. The study scope is limited to selected States in Nigeria using random sampling as well as Content Analysis (CA) method. The study concludes that since climate manifestations are global phenomenon, it is therefore, incumbent for countries in Africa, especially Nigeria (the Nigeria Government including State and Local government respectively to collaborate with organizations and agencies including music exponents to educate and create awareness about the hazards of climate manifestations and how to improve the social environmental development of the populace.